Perseroan Terbatas Syariah: Konsep dan Legalitasnya Perspektif Hukum Islam - Ainul Yaqin (Mahkamah : Jurnal Kajian Hukum Islam, 2019)
Perseroan Terbatas (en: limited liability company, PT) is one of the most important business forms and most widely applied in the modern bussines world in Indonesia. From a review of Islamic law, PT has not received much attention from thinkers regarding its legal status. In fact, financial institutions that use the Islamic label use PT as their institutional basis. Judging from contract theory, PT is identical to one of contemporary shirkah called shirkah al-musa̅hamah. Regarding the law, ulama in general are divided into two groups, some allow and others reject the validity of this shirkah. From the analysis of the contract formation mechanism and its management model, PT can be declared legitimate as part of the shirkah contract because it has the unique characteristics of the shirkah contract and fulfills the elements and conditions of the contract according to Islam. It's just that, there needs to be an adjustment in the field of business that is carried out to conform to the principles of muamalah in Islam. If this point is fulfilled, then PT can be said to be fully accepted as a legal entity according to Islam as Perseroan Terbatas Syariah.